Repetitive transcranial magnetic stimulation for late-life depression: A systematic review and meta-analysis of randomized controlled trials - Panpan Yang; Lin Li; Rui Zhang; Hailong Li (Journal of International Medical Research)
Objective Repetitive transcranial magnetic stimulation is considered a potential treatment of choice for late-life depression, but its efficacy remains unclear. Therefore, we conducted a systematic review and meta-analysis to investigate the efficacy of repetitive transcranial magnetic stimulation. Methods We systematically searched PubMed, Embase, Cochrane Library, and PsycINFO databases. Meta-analyses were performed to examine the improvement in depression measured by the Hamilton Depression Rating Scale score, response rate, and remission rate after repetitive transcranial magnetic stimulation treatment. Results A total of 10 trials were included. The pooled results revealed an improvement in the Hamilton Depression Rating Scale score (standardized mean difference:  0.51; 95% confidence interval: 0.33, 0.68), response rate (odds ratio: 2.62; 95% confidence interval: 1.37, 5.01), and remission rate (odds ratio: 6.88; 95% confidence interval: 2.93, 16.14). The pooled results of trials using repetitive transcranial magnetic stimulation with an intensity of ≥100% resting motor threshold revealed an improvement in the Hamilton Depression Rating Scale score (standardized mean difference:  3; 95% confidence interval: 1.87, 4.12) and response rate (odds ratio: 2.56; 95% confidence interval: 1.58, 4.13). No differences were observed in the pooled results of trials using repetitive transcranial magnetic stimulation with an intensity of <100% resting motor threshold. Conclusion Repetitive transcranial magnetic stimulation is effective in the treatment of late-life depression, especially with an intensity of ≥100% resting motor threshold. Future studies with larger sample sizes and long-term outcomes are still needed to provide more robust evidence. INPLASY registration number: INPLASY202550075